Analysis of the Impact of Policy and Political Economics in The Development of The Rattan Craft Industry in Cirebon - Haryono Haryono; Titik Sumarti; Didin S Damanhuri; Sofyan Sjaf (Universitas Muhammadiyah Tangerang, 2022)
ABSTRACTThe rattan handicraft industry is growing rapidly, supported by government policies in the rattan trading system and people who have expertise and skills in managing rattan into household handicraft products. The presence of this industry creates a pattern of relations in it as a symptom of political economy, where the pattern of relations which generally involves business and political relations develops into a pattern of relations between actors in the economy itself. These actors take advantage of the rattan industry for profit (rent-seeking) improperly or through transaction processes outside the economy. The results showed that the dynamics of the rattan industry development were highly dependent on government policies in the raw rattan trading system. The production process involves exporters, pengesub, raw material traders, and local traders. The rattan industry creates a relationship pattern in the form of exploitation and cooperation with three types of socio-economic-political relations between actors in the rattan handicraft industry. Rent-seeking can be categorized into local, national, and global rent-seeking.Keywords: rattan handicraft industry, political economy, rent-seeking actorsABSTRAKIndustri kerajinan rotan berkembang dengan pesat didukung oleh kebijakan pemerintah dalam tataniaga rotan dan masyarakat yang memiliki keahlian dan keterampilan dalam mengelola rotan menjadi produk-produk kerajinan rumah tangga. Hadirnya industri ini menimbulkan pola relasi di dalamnya sebagai suatu gejala ekonomi politik, dimana pola relasi yang pada umumnya melibatkan relasi bisnis dan politik berkembang menjadi pola relasi antar aktor dalam ekonomi itu sendiri. Aktor- aktor ini memamfaatkan industri rotan untuk mendapatkan keuntungan (rent-seeking) dengan tidak wajar atau melalui proses transaksi di luar ekonomi. Hasil penelitian menunjukkan bahwa dinamika perkembangan industri rotan sangat tergantung dari kebijakan pemerintah dalam tataniaga rotan mentah. Proses produksi melibatkan aktor-aktor eksportir, pengesub, pedagang bahan baku dan pedagang lokal. Industri rotan menimbulkan pola relasi yang berbentuk eksploitasi dan juga Kerjasama dengan tiga tipe sosial ekonomi politik relasi aktor dalam industri kerajinan rotan. Rent seeking dapat dikategorikan ke dalam rent seeking lokal, nasional dan global.Kata Kunci: Industri kerajinan rotan, ekonomi politik, aktor rent-seeking